Do monocular myopia children need to wear glasses? Effects of monocular myopia on visual function and binocular balance - Xiang, Aiqun; Du, Kaixuan; Fu, Qiuman; Zhang, Yanni; Zhao, Liting; Yan, Li; Wen, Dan (Frontiers in Neuroscience, 2023)
Objective This study aims to compare the binocular visual functions and balance among monocular myopic adolescents and adults and binocular low myopic adolescents and explore whether monocular myopia requires glasses. Methods A total of 106 patients participated in this study. All patients were divided into three groups: the monocular myopia children group (Group 1 = 41 patients), the monocular myopia adult group (Group 2 = 26 patients) and the binocular low myopia children group (Group 3 = 39 patients). The refractive parameters, accommodation, stereopsis, and binocular balance were compared. Results The binocular refractive difference in Group 1, Group 2, and Group 3 was −1.37 ± 0.93, −1.94 ± 0.91, and −0.32 ± 0.27 D, respectively. Moreover, uncorrected visual acuity (UCVA), spherical equivalent (SE) and monocular accommodative amplitude (AA) between myopic and emmetropic eyes in Group 1 and Group 2 were significantly different (all P < 0.05). There was a significant difference in the accommodative facility (AF) between myopic and emmetropic eyes in Group 2 (t = 2.131, P = 0.043). Furthermore, significant differences were found in monocular AA (t = 6.879, P < 0.001), binocular AA (t = 5.043, P < 0.001) and binocular AF (t = −3.074, P = 0.003) between Group 1 and Group 2. The normal ratio of stereopsis according to the random dots test in Group 1 was higher than in Group 2 (χ2 = 14.596, P < 0.001). The normal ratio of dynamic stereopsis in Group 1 was lower than in Group 3 (χ2 = 13.281, P < 0.001). The normal signal-to-noise ratio of the binocular balance point in Group 1 was lower than Group 3 (χ2 = 4.755, P = 0.029). Conclusion First, monocular myopia could lead to accommodative dysfunction and unbalanced input of binocular visual signals, resulting in myopia progression. Second, monocular myopia may also be accompanied by stereopsis dysfunction, and long-term uncorrected monocular myopia may worsen stereopsis acuity in adulthood. In addition, patients with monocular myopia could exhibit stereopsis dysfunction at an early stage. Therefore, children with monocular myopia must wear glasses to restore binocular balance and visual functions, thereby delaying myopia progression.